Novel peanut-specific human IgE monoclonal antibodies enable screens for inhibitors of the effector phase in food allergy - Suber, Jada; Zhang, Yugen; Ye, Ping; Guo, Rishu; Burks, A. Wesley; Kulis, Michael D.; Smith, Scott A.; Iweala, Onyinye I. (Frontiers in Immunology, 2022)
Background: 10% of US residents have food allergies, including 2% with peanut allergy. Mast cell mediators released during the allergy effector phase drive allergic reactions. Therefore, targeting sensitized mast cells may prevent food allergy symptoms. Objective: We used novel, human, allergen-specific, IgE monoclonal antibodies (mAbs) created using human hybridoma techniques to design an in vitro system to evaluate potential therapeutics targeting sensitized effector cells. Methods: Two human IgE mAbs specific for peanut, generated through human hybridoma techniques, were used to sensitize rat basophilic leukemia (RBL) SX-38 cells expressing the human IgE receptor (FcεRI). Beta-hexosaminidase release (a marker of degranulation), lipid mediator release, cytokine production, and phosphorylation of signal transduction proteins downstream of FcεRI were measured after stimulation with peanut. Degranulation was also measured after engaging inhibitory receptors CD300a and Siglec-8. Results: Peanut-specific human IgE mAbs bound FcεRI, triggering degranulation after stimulation with peanut in RBL SX-38 cells. Sensitized RBL SX-38 cells stimulated with peanut increased levels of phosphorylated SYK and ERK, signal transduction proteins downstream of FcεRI. Engaging inhibitory cell surface receptors CD300a or Siglec-8 blunted peanut-specific activation. Conclusion: Allergen-specific human IgE mAbs, expressed from human hybridomas and specific for a clinically relevant food allergen, passively sensitize allergy effector cells central to the in vitro models of the effector phase of food allergy. Peanut reproducibly activates and induces degranulation of RBL SX-38 cells sensitized with peanut-specific human IgE mAbs. This system provides a unique screening tool to assess the efficacy of therapeutics that target allergy effector cells and inhibit food allergen-induced effector cell activation.